(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
The present research aims to examine the motivational profile of students in the 4th grade of primary school, with particular reference to the preferred motives of promising talents. Furthermore, it aims to analyse and compare the results of the self-assessment tests of the students with the responses of the teachers referring to motivation on the talent rating scale. It is also a purpose of my research to help the students of our school as well as its teachers of the 5th-8th grades and the parents by recognising gifted students and thus to prevent their talent from being wasted. By creating a motivational profile for every 4th grade student, I offer parents and teachers an instrument that can encourage students to work and learn effectively and successfully through individual attention and treatment, using the right motivation. Withthe help of pedagogical research, I explore the students’ preferred motives, the knowledge of which can greatly influence and help the teaching-learning process.